PARTICIPANTS' EXPECTATIONS AND LEARNING NEEDS IN AN ONLINE PROFESSIONAL DEVELOPMENT INITIATIVE CONCERNING “EMERGENCY REMOTE EDUCATION” DURING THE 2020 COVID-19 LOCKDOWN - Antonella Poce (Italian Journal of Educational Technology, 2021)
During the lockdown due to the COVID-19 pandemic, several online initiatives have been enacted to provide teachers and educators with the skills needed to face the transition to online learning and teaching. Voluntary attendance of these kinds of initiatives for continuous professional development can be considered as a self-directed learning strategy enabling users to reduce a perceived skill gap. In this work, we explore and describe the expectations and the perceived learning needs of a group of participants who voluntarily decided to attend a webinar series concerning “Emergency Remote Education”, carried out by the European Distance E-learning Network (EDEN). The data collected through a short questionnaire, filled in by 607 participants, show that more than 50% of the respondents self-assessed their level of expertise as high. The results may provide insights into how to design online continuous professional development initiatives which are open to different targets.